Solutions positives maximale et minimale d’une classe de probl`emes aux limites avec des conditions nonlocales - ASSIA, MAIZA; SARA, BELLA BACI (university of eloued جامعة الوادي, 2023)
بعد تقديم المقدمات على وجه التحديد فيما يتعلق بحساب التفاضل والتكامل ذو رتبة كسرية وبعض عناصر التحليل الكسري، قدمنا مثالين عن المسائل الحدية بشروط غير محليه، المنهجية المستخدمة هي نظر ية أرز يلا أسكولي ونظر ية االنقطة الثابتة لشودر، مصحوبة بجميعAfter introducing preliminaries specifically concerning the fractional calculus and some elements of functional analysis, we presented two examples of boundary problems with non-local condition. The method used is Arzela -Ascolis theorem and Schauder fixed point theorem, accompanied by all the proofs.
mémoer master matimatuque
Keywords: الحل الموجب، نظر ية النقطة الصامدة لشودر، شروط غير محلية مسألة القيمة; Positive solution, Shauder fixed point theorem, non local condition, boundary value problem of fracional order.